Application of constitutional principles in judicial enforcement - Oksana N. Shupitskaya (Правоприменение)
The subject. Constitutional principles as phenomenon that attracts increasing attention of researchers in the development of post-soviet national legal systems.The purpose of the paper. The purpose of this study is to reveal the relationship between constitutional principles and law enforcement.The methodology of the study. The author of the study used general scientific methods of cognition: analysis, synthesis, abstraction, as well as applied practical methods such as statistical and case-method. The research is also based on the regulatory legal acts  and judicial practice, as well as on the opinions of representatives of legal science in the analyzing sphere. The main results and scope of their application. There are several reasons for scientific attention to constitutional principles. On the one hand this is connected with the increasing interest in natural law, forms of its manifestation, in the crisis conditions of the development of modern States and societies. On the other hand, on the territory of the post-Soviet states, the sphere of law enforcement is at the stage of its reform, as are the national legal systems themselves. In this regard, the search for effective methods of improving legal institutions and law enforcement relations becomes urgent. This method, according to the author, could be natural law in such a form of its manifestation as constitutional and legal principle.Constitutional principles as fundamental principles (ideas, requirements) fixed in the norms of law or followed from them. They reflect the essence of law and determine the content and procedure for the implementation of legal regulations in socially significant situations, determine the law enforcement sphere of the state. Judicial law enforcement is a complex process.  As a result of their functioning a legal prescription as a model of behavior through the activities of a special subject - the court is embodied in real social relations.Conclusions. The constitutional principles at various levels, from ideas to specific regulations, relating to state and society in general and specific to their individual institutions, serve as the basis of law enforcement. They determine judicial activities, the subjects of law enforcement, procedure, jurisdiction, establish its boundaries and a measure of its quality.